Philippine Civil Society and WTO negotiations Opportunities and challenges. [article]. - Tadem, Teresa S.
The essay discusses how civil society has found an opening in intervening in the decision-making process on the country's negotiating position in the World Trade Organization (WTO). It particularly looks at political opportunity structures which made this possible including the following external and domestic factors : 1) the anti-globalization movement which as pressured states to be more transparent and accountable to the manner in which WTO policymaking is being undertaken, 2) the failure of the Uruguay Round to provide the economic benefits to the Philippines including the government to be more open to civil society intervention, 3) the effort of the Department of Agriculture (DA), the lead agency for the negotiations of the WTO's (Re) Negotiations on the Agreement on Agricutlure (TF_WAR), adn 4) the emergence of coalition-building in the WTO, particularly among developing counties. However, there are also challenges which civil society groups face such as the need for the active involvement of the legislators in the WTO negotiations; the institutionalization of civil society participation at the local and global levels; and the prioritization of civil society strategies on dealing with the WTO and their respective governments. -- (from the author)
Keywords: Political Science-Periodicals.; Word Trade Organization (WTO).; Globalization; TF-WAR.; Philippine civil society; Political opportunity structures